2015
DOI: 10.1109/jstsp.2015.2465310
|View full text |Cite
|
Sign up to set email alerts
|

Low Computational Enhancement of STFT-Based Parameter Estimation

Abstract: Short-time Fourier transform (STFT) is one of the most widely used tools to analyze frequency and phase of local sections of time-varying signals using a time window function. Since the fixed window size of STFT causes limitation in time-frequency representation (TFR), adaptive STFT (ASTFT) techniques have been studied to adjust the window size depending on the local signal characteristics. However, ASTFT techniques suffer from heavy computational complexity in general. In this paper, we propose low computatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…The modern digital methods are based on an application of the discrete Fourier transform (DFT) or computationally optimized fast Fourier transform (FFT) [19][20][21]. The common method for a consequent spectrum estimation based on the Fourier transform is a short-time Fourier transform (STFT) [22,23].…”
Section: The Motivation For Modernization Of Solar Radio Spectrographmentioning
confidence: 99%
“…The modern digital methods are based on an application of the discrete Fourier transform (DFT) or computationally optimized fast Fourier transform (FFT) [19][20][21]. The common method for a consequent spectrum estimation based on the Fourier transform is a short-time Fourier transform (STFT) [22,23].…”
Section: The Motivation For Modernization Of Solar Radio Spectrographmentioning
confidence: 99%
“…This equation (1)(2)(3)(4)(5)(6)(7)(8)(9) leads to the motivation for defining the PSD in (1-8). The PSD can also be defined as:…”
Section: Power Spectral Densitymentioning
confidence: 99%
“…Kim et al [8] suggested a less computational improved time-based and spectral constraints approximation methods for SIFT output of radar signals. This method enhanced the spectral resolution of a received radar signal by utilizing the STFT outputs.…”
Section: Existing Surveymentioning
confidence: 99%
“…The recognition, feature extraction and monitoring analysis and other technologies of variety of physiological signals including EEG signal has become a hot topic of research in recent years [1]. All kinds of analysis methods such as Fourier transformation [2][3][4], Short Time Fourier transformation [5][6][7],wavelet and wavelet package transformation [8][9][10][11][12], Hilbert-Huang Transformation (HHT) [13][14][15][16][17] and other technologies have been applied to analysis of signal. Fourier transformation is the basic of analysis of time domain and frequency domain for signal, and is very valid to the analysis of periodic stable signal.…”
Section: Introductionmentioning
confidence: 99%